Association between dietary inflammatory index and risk of chronic kidney disease and low glomerular filtration rate; a systematic review and meta-analysis of observational studies - Amirhossein Ataei Kachouei; Frazam Kamrani; Neda S. Akhavan; Fahimeh Haghighatdoost (Journal of Health, Population and Nutrition)
Abstract Objective Earlier studies on the association between the dietary inflammatory index (DII) and the risk of chronic kidney disease (CKD) and low estimated glomerular filtration rate (low-eGFR) have provided uncertain findings. Therefore, this study aimed to summarize the existing literature on the association between DII and CKD and low-eGFR. Methods In April 2024, PubMed, Scopus, and Web of Science were searched for observational studies, along with manual inclusion of Google Scholar and Embase. The review was submitted to PROSPERO (CRD42024536756) and conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement guidelines. Studies which reported risk for CKD or low-eGFR were included. Results The random-effects model was used for statistical analysis and pooled effect sizes were reported as odds ratios (ORs) and their corresponding 95% confidence intervals (CIs). A total of 13 studies, all with a cross-sectional design, were identified eligible for inclusion in the meta-analysis. The results revealed that higher DII scores were associated with significantly higher odds of CKD (OR: 1.36, 95% CI: 1.20–1.56, p < 0.001) and low-eGFR (OR: 1.58, 95% CI: 1.26-2.00, p = 0.001). Conclusion This study found a significant positive association between the DII and the odds of CKD and low-eGFR, suggesting a higher likelihood of CKD in individuals who adhere to a pro-inflammatory diet. Large-scale prospective cohort studies are required to confirm these findings, particularly by assessing different indicators of kidney function.